The role of the zinc finger protein ZC3H32 in bloodstream-form Trypanosoma brucei - Klein, Cornelia Andrea; Terrao, Monica; Clayton, Christine (PLOS ONE, 2017)
Kinetoplastids rely heavily on post-transcriptional mechanisms for control of gene expression, with regulation of mRNA processing, translation and degradation by RNA-binding proteins. ZC3H32 is a cytosolic mRNA-binding protein with three non-canonical CCCH zinc finger domains. It is much more abundant in bloodstream-form Trypanosoma brucei than in procyclic forms. Tethering of ZC3H32 to a reporter mRNA suppressed translation and resulted in mRNA degradation, and deletion analysis suggested that this activity was present in both the N- and C-terminal domains, but not the central zinc finger-containing domain. Tandem affinity purification, however, revealed no interaction partners that might account for this activity. RNASeq analyses did not yield any evidence for sequence-specific binding or regulation of specific mRNAs. The presence of ZC3H32 homologues in monogenetic and free-living Euglenids also argues against a role in developmental regulation, although its function may have diverged in evolution. T. brucei ZC3H32 might be implicated in basal mRNA metabolism, with this role perhaps being taken over by another protein in procyclic forms.